2022
DOI: 10.1111/aman.13714
|View full text |Cite
|
Sign up to set email alerts
|

Belief correlations with parental vaccine hesitancy: Results from a national survey

Abstract: We conducted a nationally representative survey of parents' beliefs and self-2 reported behaviors regarding childhood vaccinations. Using Bayesian selection among 3 multivariate models, we found that beliefs, even those without any vaccine or health content, 4 predicted vaccine hesitant behaviors better than demographics, social network effects, or 5 scientific reasoning. The multivariate structure of beliefs combined many types of ideation that 6 included concerns about both conspiracies and side effects. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…We can further investigate these patterns using the items about expert recommendations (Table 5.9). Examining the question about accepting expert recommendations from medical doctors individually, we see the most commonly measured pattern in the literature: Black respondents were less accepting of recommendations by the medical establishment than were White respondents (matching findings by, for example, Westergaard et al, 2014;Bogart et al, 2021;and Matthews et al, 2022). However, we also see that fewer White Republican respondents than White Democratic respondents said that they would accept recommendations from medical doctors.…”
Section: Case Study Of Acceptance Of Expert Recommendations and Insti...mentioning
confidence: 65%
See 1 more Smart Citation
“…We can further investigate these patterns using the items about expert recommendations (Table 5.9). Examining the question about accepting expert recommendations from medical doctors individually, we see the most commonly measured pattern in the literature: Black respondents were less accepting of recommendations by the medical establishment than were White respondents (matching findings by, for example, Westergaard et al, 2014;Bogart et al, 2021;and Matthews et al, 2022). However, we also see that fewer White Republican respondents than White Democratic respondents said that they would accept recommendations from medical doctors.…”
Section: Case Study Of Acceptance Of Expert Recommendations and Insti...mentioning
confidence: 65%
“…Prior studies have shown that, compared with White Americans, Black Americans have a tendency toward less acceptance of expert recommendations and more endorsement of related ideas, such as conspiracy theories (Uscinski and Parent, 2014;Westergaard et al, 2014;Bogart et al, 2021;Matthews et al, 2022). This has been most evaluated, however, specifically in the context of acceptance of recommendations by medical experts.…”
Section: Case Study Of Acceptance Of Expert Recommendations and Insti...mentioning
confidence: 99%
“…2019; Lewandowsky, Gignac, and Oberauer 2013; Matthews et al. 2022; Nowak et al. 2020), which we processed through an unrotated principal component analysis in the same manner as we did independently for the magical thinking items.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, the COVID-19 pandemic ended in a state of global SARS-CoV-2 endemicity: Infection levels were brought into a steady state by population immunity, and that was achieved either through natural infection or vaccination. As with nonpharmaceutical infection control measures, compliance with vaccination fundamentally is a choice heavily influenced by cultural factors (Matthews et al, 2022). Cultural tightness is a measure of a society's emphasis on following rules simply because they are rules, while cosmopolitanism is a measure of a society's willingness to tolerate those who violate social norms and expectations.…”
Section: Engineered Pathogensmentioning
confidence: 99%